The Serendipity of Viral Trans-Neuronal Specificity: More Than Meets the Eye - Beier, Kevin Thomas (Frontiers in Cellular Neuroscience, 2021)
Trans-neuronal viruses are frequently used as neuroanatomical tools for mapping neuronal circuits. Specifically, recombinant one-step rabies viruses (RABV) have been instrumental in the widespread application of viral circuit mapping, as these viruses have enabled labs to map the direct inputs onto defined cell populations. Within the neuroscience community, it is widely believed that RABV spreads directly between neurons via synaptic connections, a hypothesis based principally on two observations. First, the virus labels neurons in a pattern consistent with known anatomical connectivity patterns. Second, few glial cells appear to be infected following RABV injections, despite the fact that glial cells are abundant in the brain. However, there is no direct evidence that RABV can actually be transmitted through synaptic connections. Here we review the immunosubversive mechanisms that are critical to RABV’s success for infiltration of the central nervous system (CNS). These include interfering with and ultimately killing migratory T cells while maintaining levels of interferon (IFN) signaling in the brain parenchyma. Finally, we critically evaluate studies that support or are against synaptically-restricted RABV transmission and the implications of viral-host immune responses for RABV transmission in the brain.